William Perry and Chris Peterson traversing muddy roads on Old Highway 8, south of New Brighton (New Brighton Area Historical Society, PO Box 120624, New Brighton, MN 55221)
e297760cc7fee303e456b313918128c1
United States
Minnesota
Ramsey
New Brighton
e297760cc7fee303e456b313918128c1
Keywords: New Brighton; Old Highway 8; Rosacker's Greenhouse; Stinson Boulevard; Perry, William; Peterson, Chris; Transportation